Cementless knee arthroplasty: a review of recent performance. (19th January 2021) - Asokan, Ajay; Plastow, Ricci; Kayani, Babar; Radhakrishnan, Ganan T.; Magan, Ahmed A.; Haddad, Fares S.
Abstract : Cementless knee arthroplasty has seen a recent resurgence in popularity due to conceptual advantages, including improved osseointegration providing biological fixation, increased surgical efficiency, and reduced systemic complications associated with cement impaction and wear from cement debris. Increasingly younger and higher demand patients are requiring knee arthroplasty, and as such, there is optimism cementless fixation may improve implant survivorship and functional outcomes. Compared to cemented implants, the National Joint Registry (NJR) currently reports higher revision rates in cementless total knee arthroplasty (TKA), but lower in unicompartmental knee arthroplasty (UKA). However, recent studies are beginning to show excellent outcomes with cementless implants, particularly with UKA which has shown superior performance to cemented varieties. Cementless TKA has yet to show long-term benefit, and currently performs equivalently to cemented in short- to medium-term cohort studies. However, with novel concepts including 3D-printed coatings, robotic-assisted surgery, radiostereometric analysis, and kinematic or functional knee alignment principles, it is hoped they may help improve the outcomes of cementless TKA in the long-term. In addition, though cementless implant costs remain higher due to novel implant coatings, it is speculated cost-effectiveness can be achieved through greater surgical efficiency and potential reduction in revision costs. There is paucity of level one data on long-term outcomes between fixation methods and the cost-effectiveness of modern cementless knee arthroplasty. This review explores recent literature on cementless knee arthroplasty, with regards to clinical outcomes, implant survivorship, complications, and cost-effectiveness; providing a concise update to assist clinicians on implant choice. Cite this article: Bone Jt Open 2021;2(1):48–57.